Pallidal activity in myoclonus dystonia correlates with motor signs. Issue 7 (16th April 2015) - Welter, Marie‐Laure; Grabli, David; Karachi, Carine; Jodoin, Nicolas; Fernandez‐Vidal, Sara; Brun, Yohann; Navarro, Soledad; Rogers, Alister; Cornu, Philippe; Pidoux, Bernard; Yelnik, Jérôme; Roze, Emmanuel; et al.
Abstract Background Myoclonus–dystonia related to epsilon‐sarcoglycan gene mutations is characterized by myoclonic jerks and mild to moderate dystonia. The role of basal ganglia dysfunction in the pathogenesis is unknown. Methods Pallidal neuronal activity was recorded in six myoclonus–dystonia and six primary generalized dystonia patients operated on for internal globus pallidus deep brain stimulation. Results In myoclonus–dystonia patients compared with primary‐dystonia patients, internal pallidum neurons showed higher burst frequency, lower mean burst, and pause durations. External pallidum neurons showed higher mean pause frequency. Oscillatory activity was present in 33% and 35% of internal pallidum neurons in myoclonus–dystonia and primary‐dystonia patients, respectively, predominantly in the theta frequency band (3‐8 Hz). In myoclonus–dystonia patients with more severe myoclonus, internal pallidum neurons exhibited a higher bursting activity with high intraburst frequency and lower oscillatory activity frequency. Conclusions Myoclonus–dystonia appears to be related to specific changes in internal pallidum activity, leading to disruption in striato‐pallido‐thalamo‐cortical circuits. © 2015 International Parkinson and Movement Disorder Society